1990
DOI: 10.1093/cvr/24.6.478
|View full text |Cite
|
Sign up to set email alerts
|

The area ratio of normal arterial junctions and its implications in pulse wave reflections

Abstract: In the majority of cases the area ratios are in close agreement with the theoretically predicted values for forward matched junctions. Minimal pulse wave reflections are therefore expected to arise from the junctions of a healthy arterial system. We therefore consider that, contrary to the established view, the presence of reflected waves in the central arterial system is a potential pathological phenomenon and not a characteristic of the healthy system. This may have important theoretical implications for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…This is in close agreement with the data on arteries by Suwa and co‐workers ( K A,k ~ 1·19, Suwa et al. 1963; Milnor 1989) and Papageorgiou and co‐workers ( K A,k ~ 1·14, Papageorgiou et al. 1990; Brown 1993), all favouring the constant wall‐thickness model.…”
Section: Critical Assumptionssupporting
confidence: 91%
“…This is in close agreement with the data on arteries by Suwa and co‐workers ( K A,k ~ 1·19, Suwa et al. 1963; Milnor 1989) and Papageorgiou and co‐workers ( K A,k ~ 1·14, Papageorgiou et al. 1990; Brown 1993), all favouring the constant wall‐thickness model.…”
Section: Critical Assumptionssupporting
confidence: 91%
“…When the waves encounter a change in the properties of the vessel, either at a bifurcation or a resistance element used to model the terminal vessels of our model, they are reflected and transmitted with magnitudes determined by a reflection coefficient which depend upon the properties of the vessels at the junction. From measurements of the geometrical and elastic properties of arterial bifurcations, it has been suggested that most arterial junctions are well matched for forward wave transmission so that RE0 (Papageorgiou and Jones, 1988;Papageorgiou et al, 1990). A less-well-recognised implication of this observation is that the arterial system is poorly matched for backward waves because a bifurcation well matched in one direction is necessarily ill matched in the other.…”
Section: Discussionmentioning
confidence: 99%
“…We also see that there is no reflection, C = 0 for symmetrical bifurcations if a % 1:15; This is generally referred to as the well-matched condition. Interestingly, extensive measurements of area ratios of human arterial bifurcations found a mean value a = 1.14 ± 0.03 [11]. Looking only at the coronary circulation, they found a mean value a = 1.18 ± 0.04.…”
Section: Reflection and Transmission Of Wavesmentioning
confidence: 99%